2007
DOI: 10.1002/elps.200600825
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation of sympathomimetics and β‐blockers by ligand‐exchange CE using Cu(II) complexes of L‐tartaric acid and L‐threonine as chiral selectors

Abstract: This paper deals with the use of Cu(II) complexes of L-tartaric acid or L-threonine as selectors for the chiral separation of drugs containing amino alcohol structure by ligand-exchange CE. Using Cu(II) ions as a complexing agent, a series of sympathomimetics and beta-blockers were resolved. It was found that the resolution strongly depends on selector concentration and pH. The optimum pH for complexation was 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The last chiral selector tested in this study was L-Thr which was used successfully for enantioseparation of sympathomimetics and β-blockers by Hödl et al 36 In this work L-Thr is shown to be applicable for the chiral resolution of Dns-AAs as well. In this case no testing of different metal ions was performed.…”
Section: Use Of L-threonine As Chiral Selectormentioning
confidence: 91%
“…The last chiral selector tested in this study was L-Thr which was used successfully for enantioseparation of sympathomimetics and β-blockers by Hödl et al 36 In this work L-Thr is shown to be applicable for the chiral resolution of Dns-AAs as well. In this case no testing of different metal ions was performed.…”
Section: Use Of L-threonine As Chiral Selectormentioning
confidence: 91%
“…Recently, tartaric acid-Cu(II) complex has been used as selector for the chiral separation of drugs with amino alcohol structure [148]. However, they have not been employed in real bioanalyses so far.…”
Section: Ligand-exchange Selectorsmentioning
confidence: 99%
“…Moreover, an improved separation efficiency and theoretical plate numbers could be achieved by using the permanent 1,3‐propanediamine‐coated capillaries or the addition of sodium dodecyl sulfate (SDS) micelles to the Cu(II) complex solution. Lately, by using Cu(II)‐L‐threonine complex as the chiral selector, a series of sympathomimetics and β‐blockers containing amino alcohol structure was resolved at the high optimum pH of 12.0 [].…”
Section: Cle‐capillary Zone Electrophoresis (Cze)mentioning
confidence: 99%